2013
DOI: 10.1021/am403365j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Novel Polymer-Free Nanostructured Drug-Eluting Coating for Cardiovascular Stents

Abstract: Angioplasty with stents is the most important method for the treatment of coronary artery disease (CAD). However, the drug-eluting stents (DES) that are widely used have the increased risks of inflammatory reactions and late stent thrombosis (LST) because of the persistence of the polymer coatings. To improve the biosafety, a novel polymer-free-composite drug-eluting coating composed of magnetic mesoporous silica nanoparticles (MMSNs) and carbon nanotubes (CNTs) was constructed using the electrophoretic deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 54 publications
0
49
0
Order By: Relevance
“…However, the widely used drug‐eluting stents (DES) have increased risks of inflammatory responses and late stent thrombosis (LST) due to the polymer coatings. It has been shown that the magnetic mesoporous Si NPs and CNTs, a novel polymer‐free composite drug‐eluting coating, exhibited excellent mechanical flexibility, blood compatibility, drug‐loading and release performance in vitro , as well as accelerating re‐endothelialization process in vivo …”
Section: Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the widely used drug‐eluting stents (DES) have increased risks of inflammatory responses and late stent thrombosis (LST) due to the polymer coatings. It has been shown that the magnetic mesoporous Si NPs and CNTs, a novel polymer‐free composite drug‐eluting coating, exhibited excellent mechanical flexibility, blood compatibility, drug‐loading and release performance in vitro , as well as accelerating re‐endothelialization process in vivo …”
Section: Medical Applicationsmentioning
confidence: 99%
“…It has been shown that the magnetic mesoporous Si NPs and CNTs, a novel polymer-free composite drug-eluting coating, exhibited excellent mechanical flexibility, blood compatibility, drug-loading and release performance in vitro, as well as accelerating re-endothelialization process in vivo. 152…”
Section: Si Npsmentioning
confidence: 99%
“…Lots of methods have been introduced to hinder corrosion rate of magnesium-based materials by surface modification methods including plasma anodization [23], microarc oxidation [24], as well as polymer coating [25,26]. Among them, polymer coating not only is potential to corrosion resistance, but also can act as a drug reservoir [3,27,28]. More importantly, this technique holds the ability to be functionalized with various biomolecules including poly(lactic-co-glycolic acid) and poly(l-lactide) acid [22].…”
Section: Surface Modification Strategiesmentioning
confidence: 99%
“…The RAPA-loading capability of 316L-BMS@CNT@M/C-3 was 60.10 ± 2.43 µg/mg, and the drugs could be continuously released for up to 2 weeks. Finally, an in vivo study showed that this nanostructured DES had the benefit of rapid re-endotheliazation in the early stages in comparison with the commercial P-FBII DES, in order to reduce the risk of thrombosis [86]. Figure 6 illustrates the porous structure of ceramic coatings and the chemical structure of polymers applied to DES.…”
Section: Nanocoatingsmentioning
confidence: 99%